An audit of tumour markers requests (CEA, AFP, CA19-9) in a district general hospital. (13th March 2011) - Rahman, N; Toqeer, M; Rademaker, J; Whitehead, M; Broyd, H; Patel, M; Abdullah, M; Gordon, K
Abstract : Introduction: Tumour markers can contribute usefully to patient management, but awareness of their limitations is essential. Inappropriate testing of tumour markers has financial implications, can cause anxiety and distress to the patient, lead to unnecessary investigations and delay in reaching the correct diagnosis. Methods: The aims were to establish the extent of inappropriate requesting of tumour markers in a district general hospital, to affect change in request practice if required and produce guidelines for local use. A retrospective audit of the requests of 3 commonly used tumour markers in Gastroenterology, AFP, CEA and CA19-9 was carried out at the Conquest Hospital over a period of 3 months from December 2009 to February 2010. The requests were analysed using guidelines from the National Academy of Clinical Biochemistry (NACB), which included summaries of relevant recommendations from other clinical organisations. Results: Total requests amounted to 818, of which 356 came from GPs, 244 from outpatient and 218 from inpatient. In these 818 patients, 982 tumour markers were requested, of which 382 (39%) were appropriate; all requests from cancer multidisciplinary meetings met the NACB guidelines. 684 (70%) of requests were for CEA, of these 352 (51%) were not appropriate. AFP and CA19-9 each made up a total of 15% of requests. CA19-9 was the most inappropriately requested tumour marker at 85%, closely followed by AFP at 60%. 133 (26%) of the patients had panels of tumour markers requested while no such requests came from cancer multidisciplinary meetings. Conclusion: These results demonstrate that the majority of requests for tumour markers by non-specialists at our institution were inappropriate when compared to the national guidelines. It is reassuring that all the requests from the MDM were appropriate. Specialists should request tumour markers and locally agreed guidelines should be made available to help non-specialists. This will ensure cost effectiveness, improve patient care and reduce unnecessary investigations.